Indonesia : 2006 Article IV Consultation and Fifth Post-Program Monitoring Discussions-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Indonesia. (IMF Staff Country Reports; Country Report ;, 2006)
Despite security risks and some major natural disasters, Indonesia has continued to make steady economic progress in recent years. Recent sound macroeconomic management has calmed inflation pressures, though financial markets remain volatile. In the short term, activity should regain momentum but there are downside risks. There is scope for fiscal policy to support activity in 2006, while still firmly pursuing reduction of the public debt burden over the medium term. The authorities have done much to reduce macroeconomic vulnerabilities in recent years.